A spatial model of bank branches in Canada - Heng Chen; Matthew Strathearn (Bank of Canada, 2020)
This research aims to empirically analyze the spatial distribution of bank-branch networks in Canada. We study the market structure (both industrial and geographic concentrations) within the networks' own or adjacent postal areas. Our empirical framework considers branch density (the ratio of the total number of branches to the area size) by employing a spatial two-way fixed-effects model. Our main finding is that there are no effects associated with market structure; however, there are strong spatial socioeconomic effects from the networks' own and nearby areas. In addition, we also study the effect of spatial competition from rival banks: we find that large banks and small banks tend to avoid markets dominated by their competitors.
Keywords: L1; R3; 330; Firm dynamics; Market structure and pricing